State of the Union Addresses - Fillmore, Millard, 1800-1874 (Salt Lake City, UT : Project Gutenberg, 2004)
"State of the Union Addresses" by Millard Fillmore is a historical account containing a collection of addresses delivered by the 13th President of the United States during the early 19th century. Specifically, this work compiles Fillmore's addresses from 1850 to 1852, a transformative period in American history marked by growing tensions related to issues such as slavery, territorial expansion, and foreign policy. The opening of the collection presents Fillmore$1 (Bs first address, delivered on December 2, 1850, where he reflects on the recent passing of his predecessor and acknowledges the nation$1 (Bs grief. He articulates his views on national rights and duties, particularly emphasizing non-interventionist foreign policy and the importance of constitutional governance. Fillmore advocates for maintaining peace and neutrality with foreign nations while discussing domestic responsibilities such as the execution of laws and the management of internal affairs. His message highlights the delicate balance required to uphold the values of justice and honor in the face of political challenges, laying the foundation for the principles he would continue to address in subsequent annual sessions. (This is an automatically generated summary.)s
Release date is 2004-02-01
Produced by James Linden. HTML version by Al Haines.
Keywords: Presidents -- United States -- Messages; United States -- Politics and government -- Sources